Nicaragua : Joint Staff Assessment of the Poverty Reduction Strategy Paper Second Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The current government has succeeded in reorienting economic policies after a series of shocks and an initial weak policy response. Revised real GDP growth targets are feasible with sustained prudent macroeconomic policies and institutional reforms. The medium-term macroeconomic framework centers on sustained prudent fiscal and monetary policies. The Poverty Reduction Strategy Paper (PRSP) could include a more detailed description of the actions being implemented to strengthen the financial system. The pursuit of fiscal discipline to restore macroeconomic stability has dominated the second year of strategy implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet